Chaomyia, a new monotypic genus of Tachininae from the Qinghai-Tibet Plateau, China (Arthropoda, Insecta, Diptera, Tachinidae) - Xusheng Liu; Jiayi Ji; Youpeng Lai; Dong Zhang; Pierfilippo Cerretti; Chuntian Zhang (ZooKeys)
We erected a new genus of Tachinidae in the subfamily Tachininae, Chaomyia gen. nov. for the new species C. qinghaiensis sp. nov. from grasslands of Haiyan County, Qinghai Province, Qinghai-Tibet Plateau, China. Chaomyia gen. nov. is distinguishable from all other genera of Tachininae (Diptera: Tachinidae) based on morphological evidence. Key morphological characters include: small size (ca. 4–5 mm); eye nearly bare; lower facial margin strongly protruding forward in front of vibrissal angle; occiput with only black setulae; lower occiput bulging; bare prosternum; two postpronotal setae; 2 presutural and 3 postsutural dorsocentral setae; 3 pairs of strong marginal scutellar setae, apical setae strong and crossed; wing membrane around crossveins r-m and dm-cu darkened; male fore claws and pulvilli shorter than 5th tarsomere; and mid-dorsal depression of abdominal syntergite 1+2 not reaching hind margin of syntergite, sternites well exposed. A possible affiliation with the tribes Polideini or Ernestiini has been discussed using morphological evidence.